Acoustic methods improve the detection of the endangered African manatee - Factheu, Clinton; Rycyk, Athena M.; Kekeunou, Sévilor; Keith-Diagne, Lucy W.; Ramos, Eric A.; Kikuchi, Mumi; Takoukam Kamla, Aristide (Frontiers in Marine Science, 2023)
The African manatee (Trichechus senegalensis) is an elusive, data-deficient, and endangered species which inhabits marine and freshwater systems throughout Western and Central Africa. A major challenge in understanding the species ecology and distribution is the difficulty in detecting it using traditional visual surveys. The recent invasion of Giant Salvinia (Salvinia molesta) at the most important site for the species in Cameroon further limits their detectability and may restrict their movements and habitat use. To investigate methods’ effectiveness in detecting African manatees, we conducted monthly vessel surveys from which visual point scans, 360° sonar scans, and passive acoustic monitoring were conducted simultaneously at ten locations and over 12 months in Lake Ossa, Cameroon. Manatee detection frequency was calculated for each method and the influence of some environmental conditions on the methods’ effectiveness and manatee detection likelihood was assessed by fitting a binary logistic regression to our data. Detection frequencies were significantly different between methods (p < 0.01) with passive acoustics being the most successful (24.17%; n = 120), followed by the 360° sonar scan (11.67%; n = 120), and the visual point scan (3.33%; n = 120). The likelihood of detecting manatees in Lake Ossa was significantly influenced by water depth (p = 0.02) and transparency (p < 0.01). It was more likely to detect manatees in shallower water depths and higher water transparency. Passive acoustic detections were more effective in uninvaded areas of the Lake. We recommend using passive acoustics to enhance African manatee detections in future surveys.